The Influence of Security Check Point (SCP) 2 Security Inspection Services on Passenger Satisfaction at the Aviation Security Unit (AVSEC) of Adi Soemarmo Boyolali International Airport - Umah, Nuril Isbatul; Istiyani, Yuniar (CV. Rayyan Dwi Bharata, 2024)
Aviation Security (AVSEC) is Aviation Security Personnel who have (must) have a license or officer proficiency certificate (SKTP) given duties and responsibilities in the field of aviation security. In the quality of security check services provided by Aviation Security (AVSEC) officers at Adi Soemarmo Boyolali International Airport is very important for passengers who will use airport services. So the researcher's goal is to find out whether there is an influence of the Security Check Point (SCP) 2 security check service on passenger satisfaction and how much influence the Security Check Point (SCP) 2 security check service has on passenger satisfaction at the Adi Soemarmo Boyolali International Airport Aviation Security (AVSEC) unit. This study uses quantitative methods and the data used in this study are the results of distributing questionnaires distributed to passengers at Adi Soemarmo Boyolali International Airport in February 2024 with a total of 100 respondents, the data analysis techniques used in this study are simple linear regression analysis, T test and determination coefficient test (R2). This means that there is an effect of Security Check Point (SCP) 2 security inspection services on passenger satisfaction at the Aviation Security (AVSEC) unit of Adi Soemarmo Boyolali International Airport. The T test results show t count t table, namely 10.266 1.660 and a significant value 0.1, namely 0.024 0.1. The results of the coefficient of determination (R2) test which shows how much influence the service variable (X) has on the passenger satisfaction variable (Y) are known with an R Square value of 51.8%, which means that the service variable affects passenger satisfaction while the remaining 48.2%, which means it is influenced by other factors or variables not used in this study.